A ball dome artefact for coordinate metrology performance evaluation of a five axis machine tool. Issue 1 (2017) - Mayer, J.R.R.; Hashemiboroujeni, Heidarali
Abstract: Five-axis machine tools are increasingly used for coordinate metrology on workpieces at various stages of machining. Evaluation of the metrological capability in five axis mode using a probed reference artefact requires accessibility from various probing directions. When rotary axes handle the artefact its deflection under varying gravitational loading is also a concern. A 3D artefact is proposed consisting of a kinematically mounted Invar structure dome holding 25 precision balls. The effect of changing gravity on its geometry is quantified and it is then used to evaluate the coordinate metrology capability in five axis mode of a wCBXfZYt topology machine tool.